The state level impact of uncertainty shocks - Haroon Mumtaz; Laura Sunder-Plassmann; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2016)
This paper uses a FAVAR model with stochastic volatility to estimate the impact of uncertainty shocks on real income growth in US states. The results suggest that there is a large degree of heterogeneity in the magnitude and the persistence of the response to uncertainty shocks across states. The response is largest in Michigan, Indiana and Arkansas while the real income in New York, Alaska and New Mexico seems least sensitive to uncertainty. We relate the cross section of responses to state-level characteristics and find that the magnitude of the decline in income is largest in states with a large share of manufacturing, agriculture and construction industries, a high fiscal deficit and a more volatile housing market. In contrast, a higher share of mining industries and larger inter-governmental fiscal transfers ameliorate the impact of uncertainty.
Keywords: C15; C32; E32; 330; FAVAR; Stochastic volatility; Uncertainty shocks; Regional effects